Vacuum heat insulating material

The vacuum insulation material, featuring a core of fumed silica, radiation inhibitors, and inorganic fibers with specific fiber length distribution, addresses the challenge of maintaining compressive strength and low thermal conductivity, achieving superior insulation performance.

JP2025057797APending Publication Date: 2025-04-09AGC INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023167548
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-04-09

AI Technical Summary

Technical Problem

Conventional vacuum insulation materials face challenges in achieving optimal thermal conductivity and maintaining compressive strength at low core material densities, which affects their long-term insulation performance.

Method used

A vacuum insulation material comprising a core material made of fumed silica, radiation inhibiting components, and inorganic fibers, with a specific fiber length distribution and content ratios, sealed in a reduced-pressure environment within a gas barrier film outer bag.

Benefits of technology

The solution provides a vacuum insulation material with enhanced compressive strength and improved thermal insulation performance, maintaining low thermal conductivity while preventing core material collapse under reduced pressure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025057797000001_ABST
    Figure 2025057797000001_ABST
Patent Text Reader

Abstract

To provide a vacuum heat insulating material having a sufficiently high compressive strength of a core material and excellent heat insulation.SOLUTION: A vacuum heat insulating material comprises a core material and a gas barrier film covering the core material, where the core material is vacuum-sealed in an outer bag formed of the gas barrier film. The core material contains fumed silica, a radiation suppressing component, and inorganic fibers, where the content of the fumed silica is 50 to 90 mass%, the content of the radiation suppressing component is 3 to 30 mass%, and the content of the inorganic fibers is 2 to 30 mass% relative to the total mass of the core material, the density of the vacuum-sealed core material is equal to or less than 0.30 g / cm3, the fiber length range of the inorganic fibers is 0.1 to 10 mm, and the fiber length distribution Lw / Ln, which is expressed as a ratio of a number average fiber length Ln to a weight average fiber length Lw of the inorganic fibers, is equal to or larger than 1.05.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a vacuum insulation material. [Background technology]

[0002] Vacuum insulation materials are used in various fields such as refrigerators and water heaters. A known example of a vacuum insulation material is a vacuum insulation material in which a molded body made of a core material containing powder and fiber is vacuum sealed in an outer bag (Patent Document 1). Although vacuum insulation materials using powder as the core material have inferior initial insulation performance compared to vacuum insulation materials using only fiber such as glass fiber as the core material, they are excellent in long-term durability because they can maintain sufficient insulation performance even in a low vacuum. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] International Publication No. 2015 / 182768 Summary of the Invention [Problem to be solved by the invention]

[0004] Conventional vacuum insulation materials such as those in Patent Document 1 have room for improvement in thermal conductivity. More specifically, if the density of the core material sealed under reduced pressure can be reduced, the thermal conductivity of the vacuum insulation material will be reduced and better thermal insulation performance will be obtained. However, the lower the density of the core material used for sealing under reduced pressure, the lower the compressive strength will be, so the core material is more likely to be crushed during sealing under reduced pressure, making it difficult to maintain the low density of the core material sealed under reduced pressure.

[0005] An object of the present invention is to provide a vacuum insulation material having a core material with sufficiently high compressive strength and excellent heat insulating performance. [Means for solving the problem]

[0006] The present invention includes the following configurations. [1] A vacuum insulation material comprising a core material and a gas barrier film covering the core material, the core material being vacuum sealed in an outer bag formed of the gas barrier film, The core material includes fumed silica, a radiation suppression component, and inorganic fibers; With respect to the total mass of the core material, the content of the fumed silica is 50 to 90 mass%, the content of the radiation suppressing component is 3 to 30 mass%, and the content of the inorganic fiber is 2 to 30 mass%, The density of the core material sealed under reduced pressure is 0.30 g / cm 3 is as follows: The fiber length of the inorganic fibers is in the range of 0.1 to 10 mm. The vacuum insulation material has a fiber length distribution Lw / Ln, which is expressed as a ratio of the number average fiber length Ln to the weight average fiber length Lw of the inorganic fibers, of 1.05 or more. [2] The vacuum insulation material according to [1], wherein the inorganic fibers have a fiber length D10 of 2.4 mm or less. [3] The vacuum insulation material according to [1] or [2], wherein the fiber length spread index (D90-D10) / D50 of the inorganic fiber, expressed as the difference between the fiber length D90 and the fiber length D10 relative to the fiber length D50 of the inorganic fiber, is 0.21 or more. [4] The vacuum insulation material according to any one of [1] to [3], wherein the inorganic fibers are one or more types selected from alumina fibers, glass fibers, silica fibers, glass wool, rock wool, and silica-alumina fibers. [5] The vacuum insulation material according to any one of [1] to [4], wherein the radiation suppression component is one or more selected from the group consisting of graphite, silicon carbide, titanium oxide, tin oxide, and potassium titanate. [6] A vacuum insulation material according to any one of [1] to [5], which is produced as a flat vacuum insulation material and has a distortion of 0.25% or less when a pressure of 4400 Pa is applied to a plane in the thickness direction of the vacuum insulation material for one hour. Effect of the Invention

[0007] According to the present invention, a vacuum insulation material is provided which has a core material with sufficiently high compressive strength and excellent heat insulating performance. [Brief description of the drawings]

[0008] [Figure 1] 1 is a cross-sectional view showing a schematic configuration of a vacuum insulation material according to an embodiment. [Diagram 2] 1 is a graph showing frequency distribution based on the number of fibers versus fiber length (mm) for Fiber 4 used in Example 4 and Fiber 6 used in Example 6. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The following terms have the following meanings: The term "core material" refers to a molded body made of a raw material mixture in a vacuum insulation material, which is molded into a desired shape. The term "fumed silica" refers to fine silica particles consisting of amorphous, spherical, pore-free primary particles. Fumed silica can be obtained, for example, by vaporizing silicon tetrachloride and carrying out a gas-phase reaction in a high-temperature hydrogen flame. The term "radiation suppression component" refers to particles that suppress radiative heat transfer by reflecting or scattering infrared light, or by absorbing infrared light and then isotropically radiating the amount of the temperature increase caused by the absorption when re-radiating the light, thereby disrupting the directionality of the infrared light. "Average aggregate particle diameter D50 of fumed silica" is the volume-based cumulative 50% diameter of fumed silica determined by laser diffraction scattering. In other words, in the volume-based frequency particle size distribution of fumed silica determined by laser diffraction scattering, a cumulative curve is obtained with the total volume of the particle group taken as 100%, and the particle diameter at the point on the cumulative curve where the cumulative volume is 50% is taken as D50. "Fiber length D10 of inorganic fibers" refers to the fiber length at the point where the cumulative number is 10% in a cumulative number distribution curve where the total number in the fiber length distribution calculated by number is 100%. "Fiber length D50" refers to the fiber length at the point where the cumulative number is 50% in a cumulative number distribution curve where the total number in the fiber length distribution calculated by number is 100%. "Fiber length D90" refers to the fiber length at the point where the cumulative number is 90% in a cumulative number distribution curve where the total number in the fiber length distribution calculated by number is 100%. The fiber length distribution is determined by the frequency distribution and cumulative number distribution curve obtained by measuring the lengths of 50 or more fibers randomly in a photograph observed with an optical microscope. A numerical range expressed using "~" includes the numerical values ​​on either side of the "~" within the numerical range.

[0010] Hereinafter, an embodiment of the present invention will be described. Note that the present invention is not limited to the embodiment described below, and various modifications are possible without departing from the gist of the present invention.

[0011] [Vacuum insulation material] The vacuum insulation material according to the embodiment comprises a core material and a gas barrier film covering the core material, and the core material is vacuum sealed in an outer bag formed of the gas barrier film, and satisfies the following conditions (1) to (5). (1) The core material includes fumed silica, a radiation suppressing component, and inorganic fibers. (2) Based on the total mass of the core material, the content of fumed silica is 50 to 90 mass%, the content of the radiation suppressing component is 3 to 30 mass%, and the content of inorganic fibers is 2 to 30 mass%. (3) The density of the core material sealed under reduced pressure is 0.30 g / cm 3 The following is the result. (4) The fiber length of the inorganic fiber ranges from 0.1 to 10 mm. (5) The fiber length distribution Lw / Ln, which is expressed as the ratio of the number average fiber length Ln to the weight average fiber length Lw of the inorganic fibers, is 1.05 or more.

[0012] Fig. 1 is a cross-sectional view showing a vacuum insulation material 1 according to an embodiment. Note that the dimensions and the like shown in the drawings in the following description are merely examples, and the present invention is not necessarily limited thereto, and can be appropriately modified and implemented without departing from the gist of the present invention.

[0013] The vacuum insulation material 1 comprises a core material 10 and an outer bag 12, and the core material 10 is sealed in the outer bag 12 under reduced pressure. For example, the core material 10 is housed in an outer bag 12 made by forming a gas barrier film into a bag shape, and the opening of the outer bag 12 is sealed under reduced pressure to obtain the vacuum insulation material 1.

[0014] (Core material) The shape of the core material is typically flat, but is not limited thereto. The shape of the core material as viewed in the thickness direction can be appropriately designed depending on the application, and examples of the shape include a square, a rectangle, and a circle.

[0015] The density of the vacuum-sealed core is 0.30 g / cm 3 Less than or equal to 0.20 g / cm 3 Less than 0.18 g / cm is preferred. 3 If the density of the core material sealed under reduced pressure is equal to or less than the upper limit, the resulting vacuum insulation material has low thermal conductivity and excellent insulation performance. The core material is easy to handle, and the fumed silica and radiation suppressing components are less likely to scatter from the core material during sealing under reduced pressure. In this respect, the density of the core material sealed under reduced pressure is preferably 0.11 g / cm or less. 3 More than 0.12 g / cm is preferable. 3 More than 0.13 g / cm is preferable. 3 The above is more preferable. If the density of the core material is too high, the influence of thermal conduction of the raw material solid used in the core material will be strong, resulting in a deterioration of thermal conductivity. Conversely, if the density of the core material is too low, the influence of radiation within the core material will be strong. Therefore, in order to obtain optimal thermal conductivity, it is important to control the core material density within the above range. The lower and upper limits of the density of the core material sealed under reduced pressure can be arbitrarily combined, and preferably are 0.11 to 0.30 g / cm. 3, more preferably 0.13 to 0.20 g / cm 3 It is.

[0016] The "density of the core material sealed under reduced pressure" refers to the average density of the entire core material sealed under reduced pressure in the outer bag, and is a value measured by the following measurement method. (Measurement method) The core material is placed inside an outer bag and placed in a vacuum chamber equipped with a heat sealing function. With the pressure inside the chamber reduced to 5 Pa, the opening of the outer bag is heat sealed to seal it, and the outside of the outer bag is returned to atmospheric pressure conditions to obtain the vacuum insulation material. The weight of the core material sealed under reduced pressure is calculated from the weight of the vacuum insulation material and the weight of the exterior material. The volume is calculated from the average value of the side lengths and thickness at five points. The density is calculated from the calculated core weight and volume. This value is the density of the core material sealed under reduced pressure.

[0017] In order to easily achieve excellent insulation performance, taking into account the effects of thermal bridges that occur at the ends of the vacuum insulation material, the thickness of the core material is preferably 2 mm or more, more preferably 5 mm or more, and even more preferably 8 mm or more. The "thickness of the core material" means the average thickness of the entire core material. The thickness is measured at any five points in the core material, and the average value is defined as the thickness of the core material.

[0018] The average aggregate particle size D50 of the fumed silica used in the core material is preferably 5 to 50 μm, more preferably 5 to 30 μm, and further preferably 5 to 20 μm. If D50 is equal to or greater than the lower limit, scattering during the reduced pressure sealing step is easily suppressed. If D50 is equal to or less than the upper limit, solid heat transfer is suppressed, and excellent heat insulating performance is easily obtained.

[0019] The specific surface area of ​​the fumed silica is preferably 50 to 400 m 2 / g, more preferably 100 to 350m 2 / g, more preferably 200 to 300m 2 When the specific surface area of ​​the fumed silica is equal to or greater than the lower limit, excellent heat insulating performance is easily obtained. When the specific surface area of ​​the fumed silica is equal to or less than the upper limit, scattering during the reduced pressure sealing step is easily suppressed. The specific surface area is measured by the nitrogen adsorption method (BET method).

[0020] As an example of fumed silica, Aerosil 200 (specific surface area 200 m 2 / g, manufactured by Nippon Aerosil Co., Ltd.), Aerosil 300 (specific surface area 300 m 2 / g, manufactured by Nippon Aerosil Co., Ltd.), CAB-O-SIL M-5 (specific surface area 200 m 2 / g, manufactured by Cabot Japan Co., Ltd.), CAB-O-SIL H-300 (specific surface area 300 m 2 / g, manufactured by Cabot Japan Co., Ltd.), Leolosil QS30 (specific surface area 300 m 2 Commercially available products such as 1,2-dichlorophenyl ether (1,2-dichlorophenyl ether, manufactured by Tokuyama Corporation) can be used. The core material may contain one type of fumed silica or two or more types of fumed silica.

[0021] The content of fumed silica in the core material is 50 to 90 mass %, preferably 60 to 90 mass %, and more preferably 70 to 90 mass %, based on the total mass of the core material. When the content of fumed silica is equal to or more than the lower limit, a core material that can achieve both compressive strength and thermal conductivity can be obtained.

[0022] By making the fiber length of the inorganic fibers contained in the core material range from 0.1 to 10 mm and making the fiber length distribution Lw / Ln 1.05 or more, the compressive strength of the core material is increased, and the core material is prevented from being crushed when it is vacuum-sealed in the outer bag. As a result, the vacuum-sealed core material is maintained at a low density and has a low thermal conductivity, resulting in excellent heat insulation performance.

[0023] Ln is the number-average fiber length of the inorganic fibers, and is calculated from the number-based frequency distribution obtained by measuring the lengths of 50 or more inorganic fibers randomly in a photograph observed with an optical microscope, using the following formula (1). Lw is the weight-average fiber length of the inorganic fibers, and is calculated from the weight-based frequency distribution obtained by measuring the lengths of 50 or more inorganic fibers randomly in a photograph observed with an optical microscope, using the following formula (2). Here, Ni in equations (1) and (2) is the number of fibers in each histogram of the average length Li. A larger Lw / Ln ratio indicates a wider distribution of the fiber lengths of the inorganic fibers.

[0024]

number

[0025] If the fiber length exceeds 10 mm, the effect of solid thermal conduction of the fiber becomes large, and the thermal conductivity of the vacuum insulation material deteriorates. Also, if the fiber length is less than 0.1 mm, the effect of improving the compressive strength of the core material is low. Lw / Ln is 1.05 or more, preferably 1.10 or more, and more preferably 1.20 or more. The upper limit of Lw / Ln is not particularly limited, and can be, for example, 2.00 or less.

[0026] The fiber length spread index (D90-D10) / D50 of the inorganic fiber is preferably 0.21 or more, more preferably 0.4 or more, and even more preferably 0.6 or more. If (D90-D10) / D50 is equal to or more than the lower limit, the compressive strength of the core material is likely to be high, and a vacuum insulation material with excellent thermal insulation performance is likely to be obtained. The upper limit of (D90-D10) / D50 is not particularly limited, and can be, for example, 2.0 or less. The larger the (D90-D10) / D50, the wider the fiber length distribution of the inorganic fibers.

[0027] The fiber length D10 of the inorganic fibers is preferably 2.4 mm or less, more preferably 2.0 mm or less, and further preferably 1.8 mm or less. The fiber length D50 of the inorganic fibers is preferably 2.0 to 5.0 mm. The fiber length D90 of the inorganic fibers is preferably 3.0 to 7.0 mm.

[0028] Examples of inorganic fibers used in the core material include alumina fibers, glass fibers, mullite fibers, silica fibers, glass wool, rock wool, slag wool, silicon carbide fibers, silica-alumina fibers, silica-alumina-magnesia fibers, silica-alumina-zirconia fibers, and silica-magnesia-calcia fibers. The inorganic fibers contained in the core material may be one type or two or more types.

[0029] Inorganic fibers are useful because they cause little volatilization of gas components under vacuum, making it easy to prevent a decrease in insulation performance due to a decrease in the degree of vacuum, and have excellent heat resistance. Among these, it is preferable to use one or more types selected from alumina fiber, glass fiber, silica fiber, glass wool, rock wool, and silica-alumina fiber because they are low cost and easy to handle.

[0030] The content of inorganic fibers in the core material is 2 to 30% by mass, preferably 2 to 20% by mass, and more preferably 2 to 15% by mass, based on the total mass of the core material. When the content of inorganic fibers is equal to or greater than the lower limit, a core material having high compressive strength can be obtained. When the content of inorganic fibers is equal to or less than the upper limit, an increase in solid heat transfer due to fibers can be suppressed, and therefore a decrease in heat insulating performance can be easily suppressed.

[0031] Examples of radiation suppressing components include metal particles such as aluminum particles, silver particles, and gold particles, graphite, carbon black, silicon carbide, titanium oxide, tin oxide, and potassium titanate. From the viewpoints of improving thermal conductivity and workability, the radiation suppressing component is preferably one or more selected from graphite, silicon carbide, titanium oxide, tin oxide, and potassium titanate. The radiation suppressing component contained in the core material may be one type or two or more types.

[0032] The content of the radiation-suppressing component in the core material is 3 to 30 mass %, preferably 5 to 25 mass %, and more preferably 10 to 20 mass %, based on the total mass of the core material. If the content of the radiation-suppressing component is equal to or higher than the lower limit, deterioration of the thermal conductivity of the vacuum insulation material due to radiation within the core material can be suppressed. If the content of the radiation-suppressing component is equal to or lower than the upper limit, the effect of increasing solid heat transfer due to the radiation-suppressing component can be suppressed, making it easier to obtain excellent heat insulating performance.

[0033] As long as the effect of the present invention is not impaired, materials other than fumed silica, radiation suppression components, and inorganic fibers may be blended into the core material. Examples of the other materials include binders and porous silica. The other materials contained in the core material may be one type or two or more types. Typical examples of the binder are inorganic binders such as sodium silicate, aluminum phosphate, magnesium sulfate, magnesium chloride, etc., but are not limited thereto, and may be organic binders.

[0034] (Outer bag) The size and shape of the outer bag are not particularly limited and can be set according to the desired size and shape of the vacuum insulation material. The gas barrier film used for the outer bag is an airtight film, and a typical example is a laminated film having a sealant layer and a barrier layer, but is not limited thereto. The gas barrier film may have other layers such as an adhesive layer, a protective layer, etc. in addition to the sealant layer and the barrier layer.

[0035] The sealant layer is provided as the innermost layer of the gas barrier film. The material forming the sealant layer is not particularly limited, and examples thereof include polyolefin resins such as low-density polyethylene, medium-density polyethylene, linear low-density polyethylene (LLDPE), polypropylene, etc. The material constituting the sealant layer may be one type or two or more types. The sealant layer may have a single layer structure or a multi-layer structure.

[0036] Examples of the barrier layer include an aluminum deposition layer, an aluminum foil layer, and a metal oxide deposition layer made of alumina, silica, or the like. The aluminum deposition layer and the metal oxide deposition layer can be formed by depositing aluminum or a metal oxide onto a deposition substrate. The deposition substrate can be a resin film such as a polyethylene terephthalate (PET) film or an ethylene-vinyl alcohol copolymer (EVOH) film. The number of barrier layers in the gas barrier film is preferably 2 or more, more preferably 2 to 6, and further preferably 2 to 4.

[0037] The adhesive used in the adhesive layer is preferably an adhesive suitable for dry lamination, such as a two-component curing polyurethane adhesive, an acrylic adhesive, or an epoxy adhesive, and is particularly preferably a two-component curing polyester adhesive.

[0038] The protective layer is preferably provided on the outermost layer, but is not limited thereto, and may be provided between the barrier layer and the sealant layer, or between two barrier layers. When the gas barrier film has a protective layer, the protective layer may be one layer or two or more layers.

[0039] Examples of materials for forming the protective layer include polyamide resins such as nylon 6, nylon 66, and copolymers of nylon 66 and nylon 6, and polyester resins such as PET and polyethylene naphthalate.

[0040] The thickness of the gas barrier film is preferably 40 to 65 μm, more preferably 45 to 65 μm, and further preferably 47 to 62 μm. When the thickness of the gas barrier film is equal to or greater than the lower limit, the film strength is excellent. When the thickness of the gas barrier film is equal to or less than the upper limit, the weight of the vacuum insulation material can be reduced.

[0041] When a flat vacuum insulation material is produced and a pressure of 4400 Pa is applied to the plane in the thickness direction of the vacuum insulation material for one hour, the amount of strain is preferably 0.25% or less, more preferably 0.23% or less, and even more preferably 0.20% or less. If the amount of strain is equal to or less than the upper limit, the decrease in thermal conductivity is suppressed, and the insulation performance is excellent.

[0042] The degree of vacuum inside the outer bag of the vacuum insulation material is preferably 1×10 to obtain excellent insulation performance and to extend the life of the vacuum insulation material. 3 Pa or less, more preferably 5×10 2 Pa or less, more preferably 3×10 2 From the viewpoint of facilitating decompression inside the outer bag, the degree of vacuum inside the outer bag is preferably 1 Pa or more, and more preferably 10 Pa or more.

[0043] The total thickness of the vacuum insulation material is preferably 3 mm or more, more preferably 5 mm or more, and even more preferably 10 mm or more. The total thickness of the vacuum insulation material is preferably 40 mm or less, and more preferably 30 mm or less. The "total thickness of the vacuum insulation material" refers to the thickness of the portion excluding the edge folds (folded-back portions) at the ends of the gas barrier film.

[0044] [Vacuum insulation material manufacturing method] The method for producing a vacuum insulation material according to the embodiment is not particularly limited as long as it can produce a vacuum insulation material that satisfies the above-mentioned conditions (1) to (5). For example, the method includes a method including: preparing inorganic fibers having a fiber length in the range of 0.1 to 10 mm and a fiber length distribution Lw / Ln of 1.05 or more; press-molding a raw material mixture containing fumed silica, a radiation suppressing component, and inorganic fibers to obtain a core material; and vacuum-sealing the core material in an outer bag formed of a gas barrier film.

[0045] The method for preparing inorganic fibers having a fiber length in the range of 0.1 to 10 mm and a fiber length distribution Lw / Ln of 1.05 or more is not particularly limited, and examples thereof include a method of pulverizing a part of inorganic fibers having a fiber length of 1.5 to 10 mm with a pulverizing device such as a ball mill to widen the fiber length distribution, a method of mixing two or more inorganic fibers having different fiber lengths in the range of 0.1 to 10 mm to obtain a fiber mixture having a wide fiber length distribution, and a method of pulverizing a part of the fiber mixture with a pulverizing device. While pulverizing inorganic fibers with the same fiber length, inorganic fibers having the same fiber length may be sequentially added to the pulverizing device. When a ball mill is used, the pulverization treatment time is preferably 1 to 10 hours, more preferably 2 to 5 hours.

[0046] The method for obtaining a raw material mixture containing fumed silica, a radiation suppressing component, and inorganic fibers is not particularly limited, and examples thereof include a method using a V-type mixer, a blender equipped with an agitator, or the like.

[0047] For press molding of the raw material mixture, for example, a manufacturing device for insulating boards described in paragraphs 0013 to 0028 of JP 2016-102511 A can be used. The manufacturing device includes an upper mold having a convex portion with a reduced pressure chamber formed therein, and a lower mold having a concave portion, and a plurality of exhaust holes are formed on the surface of the convex portion on the side of the concave portion. With the raw material mixture being poured into the concave portion of the lower mold, the upper mold is lowered by a cylinder, the convex portion of the upper mold is fitted into the concave portion of the lower mold, and the reduced pressure chamber of the upper mold is reduced by a vacuum pump, thereby performing press molding while exhausting air from the raw material mixture. The thickness and density of the core material can be controlled by adjusting the amount of raw material mixture poured into the concave portion of the lower mold and the pressing pressure.

[0048] After press molding, it is preferable to heat-treat and dry the core material, which can sufficiently remove moisture contained in the raw material and further reduce the thermal conductivity of the core material. The method for heat treating the core material is not particularly limited, and examples thereof include a method of heating in a constant temperature dryer, an electric furnace, or the like. The heat treatment temperature is preferably 80 to 200°C, and more preferably 100 to 200°C. The heat treatment time is preferably 1 to 120 hours, more preferably 1 to 60 hours.

[0049] The method for vacuum sealing the core material in the outer bag is not particularly limited, and examples include a method in which the core material is stored in the outer bag, the opening of the outer bag is sealed under reduced pressure conditions, and then the outside of the outer bag is returned to atmospheric pressure conditions.

[0050] In one example, a core material is placed inside an outer bag made by overlapping two gas barrier films and sealing three sides, and the bag is placed inside a vacuum chamber equipped with a heat seal function, and the inside of the vacuum chamber is depressurized. After the inside of the vacuum chamber is depressurized to a predetermined pressure, the remaining open side of the outer bag is heat sealed to seal the bag, and the inside of the vacuum chamber is returned to atmospheric pressure. In another example, after the core material is housed in the outer bag, the air inside the outer bag may be sucked out to reduce the pressure inside the outer bag, and the outer bag may be sealed by heat sealing or the like.

[0051] The core material may be housed in an inner bag having air permeability and then sealed in an outer bag under reduced pressure. The inner bag may be any bag that is breathable and prevents the raw material from leaking out when the core material is sealed under reduced pressure. Examples of the inner bag include bags made of paper, nonwoven fabric, etc.

[0052] As described above, the vacuum insulation material according to the embodiment satisfies the above-mentioned conditions (1) to (5). In particular, by using inorganic fibers with a wide fiber length distribution, in which the fiber length range is 0.1 to 10 mm (condition (4)) and the fiber length distribution Lw / Ln is 1.05 or more (condition (5)), the compressive strength of the core material is increased. As a result, the vacuum insulation material according to the embodiment has excellent insulation performance because the core material is not easily crushed during vacuum sealing and maintains a low density, and the decrease in thermal conductivity is suppressed. The reason why the compressive strength of the core material is increased by using inorganic fibers with a wide fiber length distribution that satisfy conditions (4) and (5) is not necessarily clear. However, it is thought that the wide fiber length distribution makes it easier for the orientation of the inorganic fibers to vary, which tends to result in an isotropic increase in compressive strength. EXAMPLES

[0053] The present invention will be specifically described below with reference to examples, but the present invention is not limited to the following description. In the following examples, Examples 1 to 5 are working examples, and Examples 6 and 7 are comparative examples.

[0054] [Fiber length D10, D30, D50, D90] In a photograph of inorganic fibers observed with an optical microscope, the lengths of 50 or more randomly selected fibers were measured, and a cumulative number distribution curve was obtained in which the total number in the fiber length distribution calculated based on the number of fibers was set to 100%. The fiber lengths at which the cumulative number was 10%, 30%, 50%, and 90% were determined as D10, D50, and D90, respectively.

[0055] [Average fiber length] In a photograph of the inorganic fibers observed with an optical microscope, the lengths of 50 or more randomly selected fibers were measured, and the average value was taken as the average fiber length of the fibers.

[0056] [Ln and Lw] In a photograph of inorganic fibers observed with an optical microscope, the lengths of 50 or more randomly selected fibers were measured, and Ln was calculated from the number-based frequency distribution using the above formula (1). Also, Lw was calculated from the weight-based frequency distribution using the above formula (2). Here, Ni in formulas (1) and (2) is the number of fibers in each histogram of the average length Li.

[0057]

number

[0058] [Density of the core material sealed under reduced pressure] The weight of the core material sealed under reduced pressure was calculated from the weight of the vacuum insulation material and the weight of the exterior material. The volume was calculated from the average value of the side length and five thickness points. The density was calculated from the core material weight and volume.

[0059] [Compressive strength (amount of strain)] Each example of vacuum insulation material was placed on a horizontal surface, and a 10 kg weight was placed on the top surface in an area of ​​150 mm x 150 mm, and a pressure of approximately 4400 Pa was applied for one hour. The thickness displacement after applying a pressure of approximately 4400 Pa was measured, and the amount of strain (%) was calculated.

[0060] [Thermal Conductivity] The thermal conductivity of the vacuum insulation material was measured using a thermal conductivity measuring device HFM-436 (NETZSCH). Three samples were prepared and measured, and the average value was taken as the thermal conductivity of the vacuum insulation material. The measurement conditions were a center temperature of 25°C and a temperature difference of 20°C.

[0061] [Core material raw materials] Fumed silica 1 (average agglomerated particle size D50: 13.5 μm) Fiber 1: Glass fibers with a fiber length of 3 mm were ground for 10 minutes using a blender with an agitator (fiber length range: 0.3 to 3 mm). Fiber 2: Glass fibers with a fiber length of 6 mm were ground for 10 minutes using a blender equipped with an agitator (fiber length range: 0.5-6 mm). Fiber 3: Glass fibers with a fiber length of 3 mm and glass fibers with a fiber length of 6 mm were mixed in a mass ratio of 90:10 and ground for 10 minutes using a blender with an agitator (fiber length range: 0.5 to 6 mm). Fiber 4: Glass fibers with a fiber length of 3 mm and glass fibers with a fiber length of 6 mm were mixed in a mass ratio of 50:50 and ground for 10 minutes using a blender with an agitator (fiber length range: 0.3 to 6 mm). Fiber 5: Glass fibers with a fiber length of 3 mm and glass fibers with a fiber length of 6 mm were mixed in a mass ratio of 30:70 and ground for 10 minutes using a blender with an agitator (fiber length range: 0.3 to 6 mm). Fiber 6: Glass fibers with a fiber length of 3 mm were ground for 1 minute using a blender with an agitator (fiber length range: 2.3 to 3 mm). Fiber 7: Silica-magnesia-calcia fiber (product name "Superwool (registered trademark) Plus) bulk, D30: 227 μm, D90: 902 μm, average fiber diameter: 3 μm, manufactured by Shin-Nihon Thermal Ceramics Co., Ltd.) Radiation suppression component 1: Graphite

[0062] [Example 1] 80 parts by mass of fumed silica 1, 16 parts by mass of radiation suppression component 1, and 4 parts by mass of fiber 1 were mixed, and the raw material mixture was press-molded and heat-treated at 200°C for 1 hour to produce a flat core material with length 200 mm x width 200 mm x thickness 15 mm. The measurement results of D10, D30, D50, D90, (D90-D10) / D50, average fiber length, Ln, Lw, and Lw / Ln of fiber 1 are shown in Table 1. The three sides of two 300 mm x 300 mm gas barrier films were heat-sealed to prepare a three-sided sealed outer bag, a core material was placed inside the outer bag, and the bag was placed in a vacuum chamber equipped with a heat seal function. The pressure inside the chamber was then reduced to 5 Pa, and the opening of the outer bag was heat-sealed in this state to seal the bag, and the outside of the outer bag was returned to atmospheric pressure to obtain a vacuum insulation material.

[0063] [Examples 2-7] A vacuum insulation material was produced in the same manner as in Example 1, except that the inorganic fibers used were changed as shown in Table 1.

[0064] [Table 1]

[0065] The density, compressive strength (amount of strain), and thermal conductivity of the core material sealed under reduced pressure for the vacuum insulation materials of Examples 1 to 7 were measured and the results are shown in Table 2. Furthermore, the frequency distribution based on the number of fibers versus fiber length (mm) for Fiber 4 used in Example 4 and Fiber 6 used in Example 6 is shown in Figure 2.

[0066] [Table 2]

[0067] As shown in Table 2, the vacuum insulation materials of Examples 1 to 5, which used fibers 1 to 5 with an Lw / Ln of 1.05 or more, had smaller strain, higher compressive strength, lower thermal conductivity, and superior insulation performance than the vacuum insulation materials of Examples 6 to 7, which used fibers 6 to 7 with an Lw / Ln of less than 1.05. 2, Fiber 4 used in Example 4, which had an Lw / Ln of 1.05 or more, had a wider fiber length distribution than Fiber 6 used in Example 6, which had an Lw / Ln of less than 1.05. From these findings, it is believed that the use of inorganic fibers with a wider fiber length distribution increased the compressive strength and improved the thermal insulation performance. [Explanation of symbols]

[0068] 1. Vacuum insulation material 10 Core material 12 Outer bag

Claims

1. A vacuum insulation material comprising a core material and a gas barrier film covering the core material, the core material being vacuum sealed in an outer bag formed of the gas barrier film, The core material includes fumed silica, a radiation suppression component, and inorganic fibers; a content ratio of the fumed silica is 50 to 90 mass%, a content ratio of the radiation suppression component is 3 to 30 mass%, and a content ratio of the inorganic fiber is 2 to 30 mass%, relative to a total mass of the core material; The density of the core material sealed under reduced pressure is 0.30 g / cm 3 is as follows: The fiber length of the inorganic fibers is in the range of 0.1 to 10 mm, A vacuum insulation material, wherein the inorganic fibers have a fiber length distribution Lw / Ln, which is expressed as a ratio of the number average fiber length Ln to the weight average fiber length Lw, of 1.05 or more.

2. The vacuum insulation material according to claim 1 , wherein the inorganic fibers have a fiber length D10 of 2.4 mm or less.

3. The fiber length spread index (D90-D10) / D50 of the inorganic fiber, which is expressed by the difference between the fiber length D90 and the fiber length D10 with respect to the fiber length D50 of the inorganic fiber, is 0.21 or more. Vacuum insulation material according to claim 1 or 2.

4. 3. The vacuum insulation material according to claim 1, wherein the inorganic fibers are at least one selected from the group consisting of alumina fibers, glass fibers, silica fibers, glass wool, rock wool, and silica-alumina fibers.

5. 3. The vacuum insulation material according to claim 1, wherein the radiation suppressing component is at least one selected from the group consisting of graphite, silicon carbide, titanium oxide, tin oxide, and potassium titanate.

6. 3. The vacuum insulation material according to claim 1 or 2, wherein when a flat vacuum insulation material is produced and a pressure of 4,400 Pa is applied to a plane in the thickness direction of the vacuum insulation material for one hour, the amount of distortion is 0.25% or less.

Citation Information

Patent Citations

  • Vacuum heat-insulating material

    WO2015182768A1